2010
DOI: 10.1136/emj.2008.058750
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in the diagnosis of clinically suspected scaphoid fracture: analysis of 611 consecutive cases and literature review

Abstract: MRI is a useful and effective tool in the diagnosis of radiologically occult wrist injuries. It is feasible to do MRI scans in a timely manner in a district general hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 27 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…71 Studies show that often MRI has a higher sensitivity for occult fracture diagnosis than x-ray or CT alone. 72,73 In the reviewed trials that only used x-rays, it is possible that falsely negative radiographs were used as the reference standard. This imperfect criterion standard bias affects estimates of US operating characteristics by either decreasing the number of false negative US or increasing the number of false positives, which will falsely increase sensitivity or decrease specificity, respectively.…”
mentioning
confidence: 99%
“…71 Studies show that often MRI has a higher sensitivity for occult fracture diagnosis than x-ray or CT alone. 72,73 In the reviewed trials that only used x-rays, it is possible that falsely negative radiographs were used as the reference standard. This imperfect criterion standard bias affects estimates of US operating characteristics by either decreasing the number of false negative US or increasing the number of false positives, which will falsely increase sensitivity or decrease specificity, respectively.…”
mentioning
confidence: 99%
“…It is standard practice for patients to be immobilised in a plaster cast for 10–14 days, followed by repeated clinical examination and repeat radiographs 1, 7, 13, 14, 15. Patients may undergo serial radiographs and clinical review at intervals over several weeks until a definitive diagnosis is made 5, 8, 9, 12. It has been argued that the prevalence of true fractures is low, with 3 out of 4 patients needlessly immobilised 10, 12, 16.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has been proven to be both sensitive and specific for the detection of occult scaphoid fractures, with a suggested sensitivity and specificity of almost 100% 1, 9, 12, 13, 17, 18, 19. Performing an MRI when the patient first presents with a wrist injury has traditionally been considered impractical, due to its lack of availability particularly in rural areas, and large cost 1, 9, 12. However, many studies have suggested that MRI may actually be a more cost‐effective imaging method, allowing an earlier definitive diagnosis and the reduction in patients being overtreated 11, 16, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been recently questioned because of the costs involved in over‐treating those with no fracture. In response to this, some authors advocate using magnetic resonance imaging (MRI) early to exclude fracture as this has high sensitivity, specificity and accuracy and has been shown to be cost effective 12 . Other investigations include bone scintigraphy and computed tomography (CT).…”
Section: Diagnosismentioning
confidence: 99%